An adolescent with sickle cell anaemia experiencing disease-related complications: priapism and leg ulcer – a management challenge. (30th April 2012) - Vasconcelos, Alexandra; Prior, Ana Rita; Ferrão, Anabela; Morais, Anabela
Abstract : Sickle-cell anaemia (SCA) is a multi-system disease, associated with episodes of acute illness and progressive organ damage. Disease severity shows substantial variation and it is often a burden for adolescents. Complications such as leg ulcer and priapism have a significant impact on quality of life. There are still no definitive treatment guidelines available. Considering the embarrassing nature of priapism and the dire consequences for erectile dysfunction, it is important to inform patients, parents and providers about the relationship of SCA to prolonged painful erections. This article will review the pathophysiology and treatment options of SCA focusing the complications of leg ulcers, priapism, cholelithiasis and retinopathy. The case study of a 14-year-old boy is used to present a management challenge of multiple SCA-related complications.